2019
DOI: 10.5709/acp-0269-7
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of Exercise on Executive Function and Attention: Resistance Versus Aerobic Exercise

Abstract: Catch game average number of direction changes per trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Similar results were revealed byHill et al (2019) who investigated the differential effect of cycling at a selfselected pace and RE on cognitive functions. These authors mentioned that only the AE positively impacts both WM and Stroop tests.In disagreement with our results,Tsuk et al (2019) showed that an acute session of RE increased both attention and executive functions performances, while the AE session improved only executive functions performances. In individuals with intellectual disability, the only research designed to explore the differential effects of RE versus AE on cognitive functions assessed inhibition and cognitive planning as cognitive functions and implemented an assisted cycling exercise as AE(Ringenbach et al, 2021).…”
contrasting
confidence: 99%
“…Similar results were revealed byHill et al (2019) who investigated the differential effect of cycling at a selfselected pace and RE on cognitive functions. These authors mentioned that only the AE positively impacts both WM and Stroop tests.In disagreement with our results,Tsuk et al (2019) showed that an acute session of RE increased both attention and executive functions performances, while the AE session improved only executive functions performances. In individuals with intellectual disability, the only research designed to explore the differential effects of RE versus AE on cognitive functions assessed inhibition and cognitive planning as cognitive functions and implemented an assisted cycling exercise as AE(Ringenbach et al, 2021).…”
contrasting
confidence: 99%
“…Research from Landrigan and colleagues [ 30 ] determined that individuals with unspecified cognitive impairment saw the most improvement in tests of executive function following a minimum of four weeks of RT in typical adults. Research in the typical population has shown that acute sessions of RT increased executive functioning significantly [ 31 ]. However, in our study we used weight machines instead of free weights for the safety of our participants, which may have eliminated the need for cognitive planning during RT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that aerobic exercise improves inhibitory control using the Stroop task in humans (Fortes et al, 2018 ; Tsuk et al, 2019 ). The current study shows that HIFT is also a valid training program that exerts a positive effect on inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…The prefrontal cortex (PFC) is a brain region that plays a key role in inhibitory control tasks (Miller and Cohen, 2001 ; Munakata et al, 2011 ). Many studies have shown the positive effect of exercise on inhibitory control abilities (Browne et al, 2016 ; Peruyero et al, 2017 ; Tsuk et al, 2019 ), with one study showing a positive effect for a high-volume resistance training program on inhibitory control abilities (Fortes et al, 2018 ). In the current study, we have assessed the effects of HIFT on inhibitory control abilities, using the Stroop test that has been used widely to assess inhibitory control abilities (West and Alain, 2000 ; Zysset et al, 2001 ; Adams and Jarrold, 2009 ).…”
Section: Introductionmentioning
confidence: 99%